(untitled) (Materiali di Estetica. Terza serie, 2020)
European education is a novel in which the Franco-Lithuanian writer Romain Gary (1914-1980) narrates the strenuous struggle of a handful of Polish partisans in Poland under the “Iron Heel” of the Wermacht, during the Second World War. Pages of tenderness among young people alternate with episodes of violence and cruelty, in a dry style. The aim of the partisans is the return to an education to the values on which Europe has grown freedom, rights, respect for persons, culture.